Different methods of artificial shade for agro-silvopastoral research - Costa Varella, Alexandre (2001)
Artificial shading sources are used to simulate silvipastoral light environments and study the effect of shade on pasture. An experiment was conducted to examine the light environment and effect on pasture yield components of two artificial shading materials. Alfalfa (Medicago sativa L.) pasture was submitted to three light regimes: full sunlight (100% tramsmissivity); black shade cloth (40%) and wooden slats (45%). The pattern of light exposure for plants differed under slats and shade cloth, but light intensity and quality were similar. Alfalfa dry matter (DM) yield and leaf area index under shaded treatments were about 60% of the open pasture. Numbers of stems per m2, number of nodes and plant height were also similar in both shaded treatments, but lower than in full sunlight. Plants under shade cloth and slats had a greater leaf to stem ratio, but. leaf temperature was cooler under both shaded treatments than in full sunlight. This resulted in delayed alfalfa development. The results indicated that both slats and shade cloth can simulate the light environment under agroforestry, but they may not better represent the biological consequences.